Kinerja Termal Pasif dan Kenyamanan Ruang Dalam Arsitektur Vernakular: : Tinjauan Sistematis Berbasis PRISMA - Zuber Angkasa; Erfan M Kamil; Iskandar Ilyas; Anson Ferdiant Diem (Universitas Muhammadiyah Palembang, 2026)
Vernacular architecture is often referenced in the development of low-energy buildings, yet evidence of its thermal performance remains dispersed across the literature. This systematic review examines passive thermal performance and indoor thermal comfort in vernacular architecture, with climate-responsive design studies used as supporting evidence. Scopus was searched via Publish or Perish on May 23, 2026, for English-language publications from 2010 to 2026. Reporting followed PRISMA 2020 and PRISMA-S. Of 72 search results, 35 publications met the eligibility criteria, including 28 studies of vernacular or traditional buildings and seven application-oriented studies. Meta-analysis was not conducted because study designs and outcomes were too heterogeneous. The synthesis identified four recurring strategy groups: material systems and thermal mass; courtyard configuration and spatial organization; natural ventilation and opening control; and shading, vegetation, and solar radiation control. Associated mechanisms included temperature moderation, thermal buffering, air movement, humidity regulation, radiation control, and seasonal heat storage and release. Occupant-based studies generally indicated positive patterns in satisfaction, thermal acceptability, and adaptive comfort, although outcomes remained context-dependent. The review proposes a framework linking architectural parameters, passive strategies, environmental mechanisms, comfort indicators, and occupant responses. Vernacular principles should be tested and adapted to specific contexts rather than applied as universal solutions.